Elastic Deflection Study of Nickel‑Titanium Orthodontic Wires: 3‑Point Bending Test X Clinical Simulation Device - Sathler, Renata; de Freitas, Marcos Roberto; Soufen, Carlos Alberto [UNESP]; Zanda, Marcelo; Fernandes, Thais Maria Freire; Maranhão, Olga Benário Vieira; Garib, Daniela Gamba; Janson, Guilherme (Wolters Kluwer, 2020)
Introduction: The purpose of this study was to compare the most usual types of bending tests used to evaluate nickel-titanium orthodontic wires: the 3-point bending test and the clinical simulation device (CSD). Materials and Methods: Eleven groups of 0.014‑inch nickel‑titanium orthodontic wires of six different brands were tested. A 3342 Instron universal testing machine with a 10 N load cell was used, and the ISO 15.841 regulation was followed. T-tests were used to compare the evaluations. Results: At a deflection of 0.5 mm, the device released significantly lighter forces then the 3‑point test. However, at deflections of 1; 2 and 3 mm, the device released significantly heavier forces. Conclusion: Because of the several differences between the tests and the inconsistency of the CSD, the 3‑point bending test was elected the most reliable method to evaluate the elastic deflection of nickel-titanium orthodontic wires.
Keywords: Copper‑nickel‑titanium; orthodontic wires; titanium nickelide